Alveolar soft part sarcoma of extremity - Kaushal, Shilpa; Negi, Muninder K. (International Journal of Research in Medical Sciences, 2020)
Alveolar soft-part sarcoma (ASPS) is an extremely rare connective tissue tumor, predominantly seen in adolescents and young adults, with a female preponderance. Alveolar soft-part sarcoma (ASPS) is a slow growing tumor, but with high likelihood of metastasis, leading to high mortality. A classical histopathological feature of an alveolar pattern from the biopsy of the lesion favors the diagnosis. We report a case of 14 years old male patient who presented with a history of single painless swelling over thigh for which surgical excision was done. Histopathology was suggestive of Alveolar soft-part sarcoma (ASPS). There was no evidence of distant metastases. He was treated with external beam radiotherapy in view of vascular invasion.